MIGRATION MEASUREMENTS FROM PLASTIC PACKAGING: A SIMULATION STUDY ON INFLUENCE OF INITIAL CONCENTRATION PROFILE - Manzoli, J. E.; Rosa, F. M. L.; Silva Felix, J. [UNESP]; Monteiro, Magali [UNESP] (Polish Acad Sciences Committee Metrology & Res Equipment, 2007)
Migration of components from plastic packaging into foodstuffs or into medicines is a very important issue, concerning public health. Using experimental techniques, like gas chromatography-mass spectrometry, these essays measure total migration and specific migration of components from plastic packaging. This work presents an explanation and applications of a numerical technique tool for this measurement, allowing the comprehension of the diffusion process and the estimate of component migration in difficult or impractical measurements. As an application example, the non-uniform influence of initial concentration profile on the migration is presented, demonstrating the necessity of this profile determination for high quality considerations on involved metrology.
Keywords: migration; diffusion; packaging; simulation; chemical contamination